The importance of additional intracranial injuries in epidural hematomas: detailed clinical analysis, long-term outcome, and literature review in surgically managed epidural hematomas - Marhold, Franz; Prihoda, Romana; Pruckner, Philip; Eder, Vanessa; Glechner, Anna; Klerings, Irma; Gombos, Jozsef; Popadic, Branko; Antoni, Anna; Sherif, Camillo; Scheichel, Florian (Frontiers in Surgery, 2023)
Objective Epidural hematomas (EDH) occur in up to 8.2% of all traumatic brain injury patients, with more than half needing surgical treatment. In most patients suffering from this perilous disease, good recovery with an excellent clinical course is possible. However, the clinical course is mainly dependent on the presence of additional intracerebral injuries. Few studies comparing isolated and combined EDH in detail exist. Methods We performed a retrospective single-center study from April 2002 to December 2014. The mean follow-up time was more than 6 years. In addition to analyzing diverse clinicoradiological data, we performed a systematic literature review dealing with a detailed comparison of patients with (combined) and without (isolated) additional intracerebral injuries. Results We included 72 patients in the study. With increasing age, combined EDH had a higher incidence than isolated EDH. The mortality rate of the patients in the cohort was 10%, of which 0% had isolated EDH and 10% had combined EDH. Good recovery was achieved in 69% of patients, of which 91% had isolated EDH and 50% had combined EDH. A subgroup analysis of the different additional intracerebral injuries in combined EDH demonstrated no significant difference in outcome. A systematic literature review only identified six studies. Patients with isolated EDH had a statistically significantly lower mortality risk [relative risk (RR): 0.22; 95% CI: 0.12–0.39] and a statistically significantly lower risk of unfavorable Glasgow outcome scale score (RR: 0.21; 95% CI: 0.14–0.31) than patients with combined EDH. Conclusions An excellent outcome in patients with surgically treated isolated EDH is possible. Furthermore, patients with combined EDH or isolated EDH with a low Glasgow coma scale (GCS) score may have favorable outcomes in 50% of the cases. Therefore, every possible effort for treatment should be made for this potentially lethal injury.